Efektifitas Metode Bagdadiyah dalam Pembelajaran Membaca Al-Qur’an siswa SMP : The Effectiveness of the Bagdadiyah Method in Reading Learning Al-Qur'an students of SMP - Asfahani, Asfahani; Hajar, Ibnu (Civiliza Publishing, Indonesia., 2023)
Learning to read the Qur'an is the source of all Islamic teachings covering all aspects of human life. One of the fundamental problems is the objective condition of Muslims today, which is blindness in learning to read the Qur'an, which shows decreased achievement; this needs to be addressed immediately. This study aimed to determine the effectiveness of the bagdadiyah method in learning the Qur'an at SMP Ma'rif 1 Ponorago. This research method uses a qualitative approach. However, the data obtained varies, which is influenced by the data collection techniques. Qualitative data can assist in describing the program implementation process, while quantitative data in the form of numbers will assist in defining the frequency of information obtained. In addition, both data are needed in the analysis process. The results of his research, namely the Effectiveness of the Bagdadiyah Method in Al-Qur'an Learning at SMP Ma'rif 1 Ponorago, are also very high. This is seen from four things: spelling hijaiyah letters, pronouncing makharijul letters, knowing shifatul letters, and fluency in reading hijaiyah letters.